Cartilla didáctica de ejercicios y actividades físicas desde los programas de bienestar para la población de la Universidad de América (2019)
Sport, physical activity and / or exercise is immersed in the daily life of human beings almost as a culture, improving our quality of life depends on each one and the style chosen, for this reason it is important not to only have the knowledge at hand, but also the time to devote at least 20 minutes a day, in order to be active and avoid or help the prevention and management of diseases. For this reason, this document provides a booklet that allows an approach to the exercise in a didactic and practical way, with little time and little implementation.